2019
DOI: 10.1139/cjp-2017-0985
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the African equatorial ionization anomaly (EIA) crests during the year 2013

Abstract: This paper discusses the variability of the position and magnitude of the crests of African Equatorial Ionization Anomaly during noon and post sunset periods. Total electron content data covered the year 2013, and were obtained from a chain of global positioning system receivers in both hemispheres around 37°E longitude. Local magnetometer data were used to infer the direction and magnitude of the E × B drift, while the solar extreme ultraviolet proxy index was used as a measure of solar activity. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…In addition, the latitudinal position of the NC and SC saddled 17–22° geographic latitude (8.2–13.7°N magnetic latitude) and 2° to −11° geographic latitude (7.3–21.3°S magnetic latitude), respectively. It is important to recall that these variations are similar to those presented in Amaechi et al (2018c) but are more accurate in the present study because of the increased number of stations used and better latitudinal and temporal resolution. The new result is that the position of the T of the African EIA varies from 2.2°S to 3.0°N magnetic latitude and should not be assumed to be fixed as has been the case in several previous studies.…”
Section: Resultssupporting
confidence: 88%
“…In addition, the latitudinal position of the NC and SC saddled 17–22° geographic latitude (8.2–13.7°N magnetic latitude) and 2° to −11° geographic latitude (7.3–21.3°S magnetic latitude), respectively. It is important to recall that these variations are similar to those presented in Amaechi et al (2018c) but are more accurate in the present study because of the increased number of stations used and better latitudinal and temporal resolution. The new result is that the position of the T of the African EIA varies from 2.2°S to 3.0°N magnetic latitude and should not be assumed to be fixed as has been the case in several previous studies.…”
Section: Resultssupporting
confidence: 88%
“…Also, the vertical plasma drift velocity (Vz) which results from the interaction of the eastward electric field and horizontal magnetic field play a significant role in the transport and redistribution of plasma at low-latitude. Vz is stronger in equinox than solstice over the African longitude (Amaechi et al, 2018;Fejer et al, 1995). The implication is that the fountain effect will be stronger in equinox and more plasma will be lifted up and diffused towards the crests.…”
Section: The Winter and Semiannual Anomaliesmentioning
confidence: 96%
“…It was computed in the local noon (1200 -1700 LT) and post sunset (1900 -2200 LT) using equation 1. Both time intervals correspond to periods when the anomaly is fully developed in Africa (Amaechi et al, 2018).…”
Section: Tec Derived From Iri Model (Iri-tec)mentioning
confidence: 99%
“…Overall, we observed clear asymmetry in the distribution of ionospheric plasma over the African EIA NH and SH crests (Watthanasangmechai et al, 2015; Amaechi et al, 2019). Figure 6 shows the illustrations of how the influence of meridional neutral wind leads to EIA asymmetry in the F layer of the ionosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, with respect to diurnal and seasonal variations of the African EIA structures, our results were consistent with the results earlier reported by Kassa et al (2014), Opio et al (2015), Oryema et al (2016), Bolaji et al (2017), and Amaechi et al (2019), although each set of authors above analyzed data for only 1 year. In addition to the fact that the current study covered more data for a more robust climatology study of the African EIA structures, this study also revealed new information about the daily morphologies of the African EIA structures, starting from the EIA formative, fully formed, and decaying stages, and also the intrahemispherical and interhemispherical plasma transport within the African EIA region.…”
Section: Resultsmentioning
confidence: 99%